Pulmonary inflammation decreases with ultra-protective ventilation in experimental ARDS under VV-ECMO: a positron emission tomography study - Deniel, Guillaume; Dhelft, François; Lancelot, Sophie; Orkisz, Maciej; Roux, Emmanuel; Mouton, William; Benzerdjeb, Nazim; Richard, Jean-Christophe; Bitker, Laurent (Frontiers in Medicine, 2024)
Background Experimentally, ultra-protective ventilation (UPV, tidal volumes [VT] < 4 mL.kg−1) strategies in conjunction with veno-venous extracorporeal membrane oxygenation (VV-ECMO) are associated with lesser ventilator-induced lung injuries (VILI) during acute respiratory distress syndrome (ARDS). However, whether these strategies reduce lung inflammation more effectively than protective ventilation (PV) remains unclear. We aimed to demonstrate that a UPV strategy decreases acute lung inflammation in comparison with PV in an experimental swine model of ARDS. Methods ARDS was induced by tracheal instillation of chlorhydric acid in sedated and paralyzed animals under mechanical ventilation. Animals were randomized to receive either UPV (VT 1 mL.kg−1, positive end-expiration pressure [PEEP] set to obtain plateau pressure between 20 and 25 cmH2O and respiratory rate [RR] at 5 min−1 under VV-ECMO) or PV (VT 6 mL.kg−1, PEEP set to obtain plateau pressure between 28 and 30 cmH2O and RR at 25 min−1) during 4 h. After 4 h, a positron emission tomography with [11C](R)-PK11195 (ligand to TSPO-bearing macrophages) injection was realized, coupled with quantitative computerized tomography (CT). Pharmacokinetic multicompartment models were used to quantify regional [11C](R)-PK11195 lung uptake. [11C](R)-PK11195 lung uptake and CT-derived respiratory variables were studied regionally across eight lung regions distributed along the antero-posterior axis. Results Five pigs were randomized to each study group. Arterial O2 partial pressure to inspired O2 fraction were not significantly different between study groups after experimental ARDS induction (75 [68–80] mmHg in a PV group vs. 87 [69–133] mmHg in a UPV group, p = 0.20). Compared to PV animals, UPV animals exhibited a significant decrease in the regional non-aerated compartment in the posterior lung levels, in mechanical power, and in regional dynamic strain and no statistical difference in tidal hyperinflation after 4 h. UPV animals had a significantly lower [11C](R)-PK11195 uptake, compared to PV animals (non-displaceable binding potential 0.35 [IQR, 0.20–0.59] in UPV animals and 1.01 [IQR, 0.75–1.59] in PV animals, p = 0.01). Regional [11C](R)-PK11195 uptake was independently associated with the interaction of regional tidal hyperinflation and regional lung compliance. Conclusion In an experimental model of ARDS, 4 h of UPV strategy significantly decreased lung inflammation, in relation to the control of VT-derived determinants of VILI.